PEMANFAATAN SERBUK ECENG GONDOK (Eichornia crassipes) TERAKTIVASI DENGAN SISTEM KANTONG CELUP SEBAGAI ADSORBEN PENJERAP ION LOGAM KADMIUM (Cd) - Rochman, Mayasari Azhari; Saleh, Chairul; Yusuf, Bohari (JURNAL ATOMIK, 2017)
The research on the use of water hyacinth powder (Eichornia crassipes) activated by adsorption method as the adsorption of cadmium metal ions (Cd) using dye bag system had been done. Water hyacinth powder was activated previously using HNO3 0,3 M then characterized by FT-IR spectroscopy. Infra-red spectrum showed hydroxyl cluster (-OH) from cellulose could function as the active sites of metal adsorption. Adsorption process was done by using variant contiguous time periods of metal ions, variant concentration of metal ions and addition of the metal ions of lead (Pb) ion adsorption on metal cadmium (Cd). From the results of the study Atomic Absorption Spectrophotometer (AAS) had shown the percentage of adsorption by water hyacinth powder adsorbent which was activated at 30 minutes of optimum contiguous time with optimum concentration 100 mg/L of 57,175 mg/L and 56,441% percentage of adsorption. In addition of the metal ions of lead (Pb) ion adsorption on metal cadmium (Cd) decreased to 20,681 mg/L with the percent adsorbed at 20,415% . Keywords: , , , , , AAS.